PELATIHAN MENYUSUN KARYA TULIS ILMIAH BIDANG MANAJEMEN DAN BISNIS GUNA MENINGKATKAN KREATIVITAS SISWA MA NURUL ISLAM KARANGCEMPAKA BLUTO SUMENEP - Unsul Abrar; Moh. Kurdi; Syaiful Anwar (ABDIMASKU : Jurnal Pengabdian Masyarakat UTND, 2023)
The majority of students or students still do not quite understand the making of papers, let alone have not gone to a further stage, for example scientific papers that have to carry out further research or observations in the field, so there is a need for some activities that do prepare students or students at the madrasa to take part in several activities. training in order to understand accurately and better about the preparation of scientific papers and more specifically on scientific works in the field of management and business. methods in the form of socialization, training and practice in the preparation of simple scientific papers, in its implementation there were around 30 more students who received training specifically for grade 3 Madrasah Aliyah and the implementation of PkM on the occasion went well so that there were some results. The results obtained from this community service are, first, further understanding of scientific writing in a comprehensive manner, second, growing topics that are of interest at this time and in accordance with the interests of these students, third, students or students obtain examples of correct writing systematics about written works. scientific